Pengaruh penggunaan madu sumbawa dan madu olahan berbagai konsentrasi terhadap kualitas spermatozoa epididimis domba setelah penyimpanan dalam refrigerator - Ludfiyaningrum, Siti Diyani; Gustari, Sri (Ovozoa: Journal of Animal Reproduction, 2021)
Artificial Insemination is used to conserve genetic resources. It is necessary to preserve spermatozoa in a certain diluent at certain temperature before artificial insemination. Information regarding the use of honey in the spermatozoa diluent is still less in number. This research aims to determine the effect of Sumbawa honey and processed honey in various concentrations on the quality of spermatozoa after storage in refrigerator. The main materials used were five ram testicles. Spermatozoa was collected from cauda epididymis by mincing and adding 5 ml PBS. The sample were divided into 7 groups of treatment: 1% Sumbawa honey, 2% Sumbawa honey, 3% Sumbawa honey, 1% processed honey, 2% processed honey, 3% processed honey, and control using 0.5 gram glucose in 100 ml Tris diluent. The assessment was carried out microscopically including motility and viability. Data were analyzed statistically using one-way analysis of variance (Anova) on the SPSS statistics 16.0 program. The results showed no significant difference (p > 0.05) in the motility and viability of spermatozoa in all treatment of Sumbawa honey (1%, 2%, 3%), processed honey (1%, 2%, 3%), and control. The conclusion of this study is that honey in spermatozoa diluent has no effect on the quality of spermatozoa.